Effect of frost layer on heat transfer of cryogenic fluid in a finned tube. (July 2020) - Ren, Lemei; Jiao, Wenling; Tian, Xinghao; Liu, Tianjie
Highlights: A coupled heat transfer model is developed for a cryogenic finned-tube. Frost layer changes largely the thermal resistance of the air side, and the fluid side. The thermal resistance of the forced convection is much larger than that of flow boiling. The optimum flow rate and tube length are recommended for cryogenic vaporizer. Abstract: The current study presents a mathematical model for a single cryogenic finned tube to investigate the effect of frost layer on the heat transfer performance under natural conditions. The proposed model was validated by the experimental data comprising a wide range of air conditions and cryogenic fluid flow rates. The thermal resistance distribution and the effect of the frost layer on the outlet temperature and on the heat transfer coefficient were modeled under different operating conditions. The results revealed that the maximum thermal resistance occurs in the liquid-phase section of the tube, and the two-phase section of the tube experiences the maximum frost thermal resistance. The decrease in the heat transfer caused by the frost layer largely depends on the flow rate of cryogenic fluid, followed by air temperature, and relative humidity. Finally, increasing the tube length lessens the effect of the frost layer on the heat transfer until the tube length reaches a given threshold at a fixed ratio of tube length to cryogenic fluid flow rate.